Perception of English lexical stress by Iraqi Arabic and Chinese Malaysian ESL learners - Ali, Hasan Shaban (2017)
Lexical stress is argued to have a significant role in native speakers’ perception and control of speech (Field, 2005; Cutler, 1984). Previous studies have shown that second language learners, particularly those from a non-stress language background, may not acquire the system of stress in the second language in the same way as native speakers do in the target language (Peperkamp and Dupoux, 2002, Archibald, 1997). As the realization of stress is a significant component of L2 acquisition, miscommunication can be the result of improper assignment of the lexical stress in the second language. The study aimed to investigate the influence of the L1 stress system on the acquisition of L2 stress at the word level. Two language groups of participants took part in a speech perception task: Iraqi Arabic and Chinese Malaysian ESL learners. The researcher adopted two models of lexical stress: the Stress Deafness Model (Peperkamp & Dupoux, 2002) and the Stress Typology Model (Altmann & Vogel, 2002). One hundred and sixty nine subjects were recruited for the study; the number of subjects in each proficiency level depended on their scores in the Oxford placement test. Specifically the study addresses the following questions i) Is there any language type effect on the overall performance mean scores in the perception of lexical stress? ii) Is there any language proficiency effect on the performance of both language groups in the perception of lexical stress? iii) What are the overall mean scores in the perception of lexical stress based on match/mismatch conditions? iv) Is there any word length effect on subjects’ performance of each language group in the perception of lexical stress? v) What are the most difficult disyllabic and trisyllabic structures to be perceived by each language group? vi) Is there any word category effect on the performance of each language group in the perception of lexical stress? vii) Is there any stress position effect on the mean percentage scores of both language groups in the perception of lexical stress?The speech perception task is a stress identification task. Participants listened to real as well as nonce words and identified the location of main stress in the stimuli. As Chinese is a tonal language (non-stress language), therefore, the stimulus items presented were selected and recorded based on assumptions about stress patterns in Iraqi Arabic. The items accessed in this task either matched or mismatched the expected stress computation in Arabic. If L1 influence was present, facilitation was expected for Iraqi Arabic and not Chinese Malaysian learners. The results showed that Iraqi Arabic participants did in fact perform better in the identification of lexical stress in English real words and nonce words when the stress pattern matched stress rules in Arabic compared to the mismatched condition. No facilitation was found for Chinese Malaysian learners whose performance was not significantly different between the matched and mismatched condition, and they performed relatively poorer compared to the Iraqi Arabic participants. Both language groups were more accurate at identifying final stress position in disyllabic than initial position, whereas in trisyllabic structures the Iraqi Arabic L2 learners showed a preference for penultimate stress position in contrast with the Chinese Malaysian group who had a preference for assigning stress to the final syllable of the word. It was also shown that the ability in perceiving lexical stress was influenced by syllable structure. The rank order of performance by both groups of subjects for different syllable structures was different. That is to say, syllable structures which are easily perceived by Iraqi Arabic group are difficult to be identified by the Chinese language group and vice versa. The findings are partially inconsistent with the predictions from the Stress Typology Model and the Stress Deafness Model. The results suggest that L2 learners from predictable stress language could perceive differences in L2 stress positions at the word level and they are not “stress deaf”. In sum, the study showed that there is evidence of first language influence in lexical stress assignment, but L2 lexical stress assignment rules can be learned as performance of the subjects improved with more exposure to the language.